ON THE QUESTION OF THE RELEVANCE OF ECONOMICS AS A SCIENCE: POSTMODERN FILOSOFIA CRITIQUE - JACKSON, Emerson Abraham (Theoretical and Practical Research in Economic Fields; Vol 9 No 2 (2018): TPREF, Volume IX, Issue 2(18), Winter 2018DO - 10.14505/tpref.v9.2(18).01, 2018)
This article has adopted an open discourse in addressing pertinent concerns about the scientific existence of economics as a discipline. In doing so, some (critical) Filosofia arguments have been provided in ensuring that a well balanced approach is taken on the subject. Obviously, the approach of Popperian falsification used by economic science to address scientific justification through its varied scientific platform of technology applications like EVIEWS, STATA, MatLab and many more, have been applauded. Albeit such advances, the views of modern and postmodern critics have also come out saliently in a bid to ensuring open discourses are laid on the way forward in adding scientific credence to the subject matter. In concluding, it was acknowledged that more is needed in ensuring that economic science as practiced by economists takes an open approach to critical discourse, reflecting reality about its pursed scientific ventures, given the persistence of economic volatility manifested across the global community.